2015
DOI: 10.1136/bjophthalmol-2015-306689
|View full text |Cite
|
Sign up to set email alerts
|

B-Raf inhibition in conjunctival melanoma cell lines with PLX 4720

Abstract: Proliferation inhibition of conjunctival melanoma cells by PLX 4720 depends on their B-Raf genotype. Therefore, therapeutic application of B-Raf inhibitors should take into account the specific B-Raf genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Although JQ1 has not yet been tested as a targeted clinical agent in UM, this BETi exhibits very broad anticancer effects and has previously demonstrated inhibition of tumour growth in an animal model (Ambrosini et al, 2015), consistent with high levels of transcriptional repression revealed in our UM study (Figures 3 and 5). We extend these published findings by demonstrating that CoM cell models also exhibit sub-micromolar sensitivity to JQ1, despite GNAQ/11-wt status and the presence of a BRAF mutation in CRMM1, which sensitizes these cells to the V600E-selective BRAF inhibitors PLX4720 (Riechardt et al, 2015) and vemurafenib (PLX4032) (Figure 6a). When enrichment for mRNAs in specific canonical pathways and their associated cellular functions were analysed, the likely functional consequences on cell survival and proliferative mechanisms through kinome reprogramming by JQ1 in UM and CoM cells became apparent ( Figure 3b).…”
Section: Discussionsupporting
confidence: 79%
“…Although JQ1 has not yet been tested as a targeted clinical agent in UM, this BETi exhibits very broad anticancer effects and has previously demonstrated inhibition of tumour growth in an animal model (Ambrosini et al, 2015), consistent with high levels of transcriptional repression revealed in our UM study (Figures 3 and 5). We extend these published findings by demonstrating that CoM cell models also exhibit sub-micromolar sensitivity to JQ1, despite GNAQ/11-wt status and the presence of a BRAF mutation in CRMM1, which sensitizes these cells to the V600E-selective BRAF inhibitors PLX4720 (Riechardt et al, 2015) and vemurafenib (PLX4032) (Figure 6a). When enrichment for mRNAs in specific canonical pathways and their associated cellular functions were analysed, the likely functional consequences on cell survival and proliferative mechanisms through kinome reprogramming by JQ1 in UM and CoM cells became apparent ( Figure 3b).…”
Section: Discussionsupporting
confidence: 79%
“…; Riechardt et al. ). Unfortunately, many cutaneous melanoma patients treated with a BRAF inhibitor develop resistance, causing reactivation of the MAPK pathway (Hertzman & Egyhazi ).…”
Section: Discussionmentioning
confidence: 99%
“…BRAF inhibitors have recently been investigated in BRAF ‐mutated CM cell lines, showing promising effects of reduced CM proliferation rates (Riechardt et al. ). Apart from BRAF inhibitors being potentially useful for the treatment of advanced CM, BRAF inhibition was found to be efficient as an adjuvant treatment in a case of extensive CM without metastasis (Pahlitzsch et al.…”
Section: Discussionmentioning
confidence: 99%
“…24 The efficiency of direct BRAF inhibition in conjunctival melanoma (CJM) has been evaluated in vitro in two studies. 25,26 The response to BRAF inhibition in advanced metastatic CJM has been variable, ranging from a partial response lasting 1 month 27 to significant tumor regression peaking after 4.5 months. 28 A complete regression for 38 months of an irradiated metastatic CJM treated with vemurafenib has also been documented.…”
mentioning
confidence: 99%